Makna, Simbolisme, dan Tafsiran: Analisis Semantik dan Hermeneutik Teks Agama Buddha dalam Dhammapada dan Sutta Pitaka - Tri Wanti (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2023)
This study examines the dynamics of meaning, symbolism, and interpretation in Buddhist religious texts through semantic and hermeneutic approaches using qualitative methods. The research explores how the structure of meaning in texts such as the Dhammapada and Sutta Pitaka shapes understanding of Buddhist values, and how teachings in symbols such as the Middle Way, Three Jewels, and Nirvana undergo transformations of meaning according to cultural contexts. The findings show that the understanding of Buddhist text meanings is not fixed, but dynamic, formed through interactions between text, context, and readers. This research employs semantic analysis to identify denotative and connotative meanings, combined with hermeneutic interpretation following Gadamerian and Ricoeurian frameworks. The results reveal that Buddhist symbols carry multilayered meanings that require contextual interpretation, contributing to contemporary understanding and application of Buddhist teachings in diverse cultural settings